2016
DOI: 10.18632/oncotarget.12776
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in tonsillar cancer is associated with human papillomavirus positivity and improved survival: implications for anti-PD1 clinical trials

Abstract: In this study, we examined PD-L1 expression by immunohistochemistry in 99 patients with tonsillar cancer and known human papillomavirus (HPV) status to assess its clinical significance. We showed that the pattern of PD-L1 expression is strongly related to HPV status. The PD-L1 positivity rate was 83.3% in HPV-positive cases and 56.9% in HPV-negative cases (p < 0.05). Patients with HPV-positive/PD-L1-positive cancer had significantly better event free survival and overall survival compared with patients with HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 33 publications
4
39
0
1
Order By: Relevance
“… Importantly, in this study, we showed that HPV‐positive tumors have higher numbers of CD4+ and CD8+ cells both in the tumor and in the surrounding stroma, which might explain the higher expression of HLA‐II, both HLA‐DRA and HLA‐DP/DQ/DR, on tumor cells compared to HPV‐negative tumors. As previously observed, a positive correlation between PD‐L1 expression on immune cells and longer OS was found.…”
Section: Discussionsupporting
confidence: 88%
“… Importantly, in this study, we showed that HPV‐positive tumors have higher numbers of CD4+ and CD8+ cells both in the tumor and in the surrounding stroma, which might explain the higher expression of HLA‐II, both HLA‐DRA and HLA‐DP/DQ/DR, on tumor cells compared to HPV‐negative tumors. As previously observed, a positive correlation between PD‐L1 expression on immune cells and longer OS was found.…”
Section: Discussionsupporting
confidence: 88%
“…Human papilloma virus (HPV)/p16positive tumors had significantly lower CXCL9 expression than HPV/p16-negative tumors. A correlation between HPV-positivity and PD-L1 expression has previously been reported in oropharyngeal cancer [63]. Due to the low number of HPV/p16-positive cancers in our study, the correlation between the virus, CXCL9, and PD-L1 expression in oral cancer needs validation in a study with a higher amount of HPV-positive patients.…”
Section: Variablesupporting
confidence: 49%
“…Cancer immunotherapy, which differs from traditional cytotoxic therapies and targeted therapies, is a new class of anti-cancer drugs with promising clinical activity in different types of tumors [ 18 , 42 - 45 ]. Previous studies have reported that pemetrexed-based chemotherapy in anaplastic lymphoma kinase rearrangement patients was associated with a higher response rate and longer PFS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%